Effectiveness of shoulder injury prevention programs in an overhead athletic population: A systematic review - Wright, A. A.; Ness, B. M.; Donaldson, M.; Hegedus, E. J.; Salamh, P.; Cleland, J. A. (Physical Therapy in Sport, 2021)
Objective To analyze the effectiveness of shoulder injury prevention programs in overhead athletes.